Mathematical and experimental investigation on pressure drop of heterogeneous ice slurry flow in horizontal pipes. (May 2017) - Wang, Jihong; Wang, Shugang; Zhang, Tengfei; Battaglia, Francine
Highlights: An analytical model is developed to represent heterogeneous ice slurry flow. The proposed analytical model shows desirable accuracy, generality and efficiency. An increase in pressure drop with increasing velocity and ice fraction generally exists. Flow regimes affect sensitivities of pressure drop to variations in velocity and ice fraction. Abstract: Ice slurry as an advanced secondary refrigerant has attracted much attention due to the growing concern about energy shortage and environment protection. To promote the practical applications of ice slurry, an extensive knowledge of the pressure drop of ice slurry flow in pipes is beneficial. The available research mainly focuses on the pressure drop of ice slurry flow without considering the non-uniform distribution of ice particles within. Furthermore, the impact of the carrier fluid and ice particles on the pressure drop of ice slurry is not well documented. This investigation combined numerical, analytical and experimental methods to analyze the distributions of concentration, velocity and pressure drop in heterogeneous ice slurry flow. An analytical pressure drop model was developed based on multiphase flow dynamics to quantify the pressure drop of each phase of ice slurry flow. Experiments for laminar and turbulent ice slurry flow in horizontal pipes were used to evaluate the proposed model. The analysis revealed good agreement between the proposed model and experimental data. Moreover, the proposed analytical model is computationally efficient, which can be applied to estimate the pressure drop of ice slurry flow for most practical applications.